1970
DOI: 10.1128/jvi.6.1.87-93.1970
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Aspects of the Uptake of Simian Virus 40 by Permissive Cells

Abstract: After exposure of permissive cells to simian virus 40 (SV40), single particles were engulfed by the cell membrane and transported to the nucleus. The cell membrane closed tightly around the particles, increasing their diameter from 40 to 55 nm. The cell membrane was lost during interaction with the nuclear membranes, and particles of the original size were found in the nucleus 1 hr after infection. Uncoating of these nuclear particles occurred rapidly, and none could be found 4 hr after infection; Viral progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 18 publications
4
39
0
Order By: Relevance
“…Other viruses have means for transporting their genomes into the nucleus, without relying on the host cell's progression through mitosis. SV40 (Hummeler et al, 1970;Clever et al, 1991) and influenza virus (Martin and Helenius, 1991) particles can apparently migrate through the nuclear pore. Electron micrographs suggest that other viruses, including adenovirus (Dales and Chardonnet, 1973), granulosis virus (Summers, 1971) and herpes simplex virus (Miyamoto and Morgan, 1971;Tognon et al, 1981;Batterson et al, 1983) bind their viral cores to the nuclear pore to transfer their DNA into the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Other viruses have means for transporting their genomes into the nucleus, without relying on the host cell's progression through mitosis. SV40 (Hummeler et al, 1970;Clever et al, 1991) and influenza virus (Martin and Helenius, 1991) particles can apparently migrate through the nuclear pore. Electron micrographs suggest that other viruses, including adenovirus (Dales and Chardonnet, 1973), granulosis virus (Summers, 1971) and herpes simplex virus (Miyamoto and Morgan, 1971;Tognon et al, 1981;Batterson et al, 1983) bind their viral cores to the nuclear pore to transfer their DNA into the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on SV40 entry found the internalisation pathway to differ in several ways from the classical clathrinmediated endocytic process described for many viruses. Firstly, electron micrographs of SV40-infected cells showed the majority of particles in small tight-fitting vesicles, which appeared to be uncoated (Hummeler et al 1970). These vesicles were able to fuse to generate larger compartments within the cell (which we now term caveosomes; Maul et al 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological studies of SV-40 and polyoma virus entry have suggested, however, that all viruses may not be as disciplined in their interactions with cellular organelles. These nonenveloped viruses, which belong to the papovavirus family, have been seen to enter the cells via small tight-fitting, uncoated membrane vesicles ("monopinocytotic" vesicles) derived from the plasma membrane (13,15,19,23,24). Incoming virus particles have also been reported in a variety of cellular compartments, including the nucleoplasm, the lysosomes, the ER, and mitochondria (15,19,23,24).…”
mentioning
confidence: 99%